Implementasi Algoritma Adaptive Huffman Coding Pada Aplikasi Kamus Kedokteran Berbasis Android - Rio Parmana (Graha Mitra Edukasi, 2022)
Technological advances that continue to develop in the era of globalization demand progress from all fields that can provide convenience in presenting information and sending information, with the increasing number of current internet users the information presented is increasing, one of which is information in the form of text such as warning messages, appeals or text that describes an event in the form of text information is used more often than in other forms. The size of the file or text file can be overcome by using a compression or compression process. Compression is a process to reduce the size of a file so as to save storage space and the process of exchanging data. The Huffman algorithm compression technique is able to provide memory usage savings of up to 30%. The Huffman coding algorithm has a complexity of 0(n log n) for a set of n characters